The physiological effects of swimming competition on 16-17 year old elite female swimmers - Griffin, A. J.; Unnithan, V. B.; Ridges, P. (Pediatric Exercise Science, 1999)
Findings The results of this study showed that elite female swimmers had symptoms of acute overtraining following two days of competition. Postcompetition submaximal VO2 was significantly higher than precompetition, however there was no significant difference between pre- and postcompetition VO2 peak. The average resting blood lactate level recorded postcompetition was significantly higher than the average resting precompetition value. Resting heart rate was significantly higher postcompetition relative to precompetition values. Results from the Wingate test revealed that there was no significant difference between pre- and postcompetition anaerobic power. Implications The combination of high-intensity training and competition can lead to short-term overtraining. Short-term overtraining by itself may not cause much harm to the athlete. However, repeated bouts of short-term overtraining may lead to long-term or chronic overtraining which can have detrimental effects on the athlete's health and performance. To avoid overtraining, coaches may want to consider and balance the number of competitions swimmers are performing in and the intensity and volume of training immediately following competitions. One or two recovery workouts (long duration and low intensity) following intense competition may help athletes return to precompetition physiological status. Source: Pediatric Exercise Science. 11:22-31